Azaleas at a Glance - Sydney Park Brown; Dewayne L. Ingram; James T. Midcap (EDIS, 2012)
Spectacular flowers and shade tolerance are among the reasons for the azalea’s popularity as a landscape plant in North and Central Florida. They enhance the home landscape as foundation or mass plantings and as background or foreground plants, depending on their size. They are also sometimes pruned into single-trunked standards that serve as specimen plants. Generally, their open, relaxed growth habit is more suited to informal landscape designs. This revised 5-page fact sheet was written by Sydney Park Brown, Dewayne L. Ingram, and James T. Midcap, and published by the UF Department of Environmental Horticulture, January 2012.